All-trans retinoic acid and late relapses in acute promyelocytic leukemia: Very long-term follow-up of the North American Intergroup Study I0129 - Douer, Dan (2013)
We report a long-term follow-up (median 11.8 years) of the First North American Intergroup Study. 379 patients were randomized to induction with ATRA or to chemotherapy. All complete responders (CR) received consolidation chemotherapy, then randomized to 1 year ATRA or observation. 245 patients received ATRA sometime during the study: 195 (80%) achieved a CR. Nine (4.6%) relapsed late (>3 years from CR), the last occurred after 4.6 years; 7 of them were still alive after 5.5–15 years. In APL patients, late relapses are uncommon, and those who sustain CR >5 years can be considered cured.